Analisis Pengaruh Penggunaan Sarana Produksi Terhadap Pendapatan Usahatani Jagung di Desa Mattirotasi Kabupaten Sidenreng Rappang - Munawarah; Sumartan; Restu Ray; Lisra (Universitas Medan Area, 2024)
Corn is an important necessity for human life and is the second food crop commodity after rice in Indonesia. One of the corn production centers in Indonesia is in Sidenreng Rappang Regency, South Sulawesi Province. Corn production in this area is of concern to the government, because most of the people make their living as corn farmers. However, there are several obstacles in procuring production facilities in corn cultivation, starting from the use of less superior seeds, the procurement of expensive input facilities, the difficulty for farmers to obtain fertilizer. This research aims to analyze the influence of the use of production facilities on corn farming income in Mattirotasi Village, Watang Pulu District. The data analysis used is multiple linear regression analysis with the independent variables consisting of seeds, fertilizers and pesticides while the dependent variable is corn farming income. The results of this research show that the use of corn farmers' production facilities, namely seeds, fertilizers and pesticides in Mattiro Tasi Village, Watang Pulu District, Sidenreng Rappang Regency, has a big influence on increasing or decreasing corn farming income with a regression coefficient R2 value of 80.2% while it is 19.8%. others are influenced by factors other than fertilizer, seeds and pesticides. This shows that if these production facilities are used efficiently, farmers' corn production will increase. The large amount of corn production carried out by farmers will increase the level of farmer income.